Assessing EU Leadership in Inter-regional Relations The Case of the Institutionalisation of ASEAN Disaster Management (Taylor & Francis, 2022)
This book comparatively analyses the role of the EU in influencing the policies of other regional organisations by assessing its role in leading the institutionalisation of ASEAN disaster management institutions.
English
Keywords: International relations; Politics & government; ARPDM; ASEAN; Asia; crisis management; disaster management; disaster response; EU; EU external relations; global governance; institutionalisation; inter-regionalism